Desenvolvimento de biossensor para detecção rápida de anticorpos específicos para alérgenos derivados dos ácaros Blomia tropicalis e Dermatophagoides sp - Picolo, Bianca Uliana (2016)
Over the past years, the prevalence of allergic diseases has increased substantially in the world. Techniques such as skin prick test, ELISA and ImmunoCAP are widely used in the medical field for diagnosis of allergies. Electrochemical biosensors may be valuable approach for improvement of the allergic diseases diagnosis, because it may be more sensitive, specific and selective platform in comparison with other diagnostic technologies. This study aimed to develop multifunctional electrochemical biosensors with the streptavidin-modified surface for the detection of IgE antibodies, from allergic patients, specific to allergens from Blomia tropicalis, Dermatophagoides farinae and Dermatophagoides pteronyssinus. The biosensor produced with magnetic capture-structured was able to detect IgE antibodies from serum samples specific to whole B. tropicalis allergens and also to the major B. tropicalis allergen, Blo t 5. In addition, the biosensor developed was also able to detect IgE antibodies specific to multiple allergens from different sources of house dust mites, specially when minimal volumes of serum samples from multi-sensitized atopic individuals were probed. In conclusion, the biosensor developed in this study may be an innovative and powerful platform that may be relevant to the monitoring of respiratory allergic diseases, contributing to clinical management in allergen- specific immunotherapy and also to the healthcare promotion of patients with allergic diseases.